2015
DOI: 10.1039/c5ra02628h
|View full text |Cite|
|
Sign up to set email alerts
|

Electronic pH switching of DNA triplex reactions

Abstract: Remote electronic control of fast DNA processing reactions such as S–S-ligation is achievedviapH switching of triplex structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…This effect is reversible, and can be used to modify the pH around an electrode by several units if desired. Other electrochemical reactions can be used in a similar way and it has already been shown that it is possible to control the conformation of pH-sensitive DNA structures electrochemically 14,15 . Depending on the pH of the solution, the nanoswitch is either open or closed.…”
Section: A Catalytic Cycle With An Electrochemically Controlled Ph-sementioning
confidence: 99%
See 1 more Smart Citation
“…This effect is reversible, and can be used to modify the pH around an electrode by several units if desired. Other electrochemical reactions can be used in a similar way and it has already been shown that it is possible to control the conformation of pH-sensitive DNA structures electrochemically 14,15 . Depending on the pH of the solution, the nanoswitch is either open or closed.…”
Section: A Catalytic Cycle With An Electrochemically Controlled Ph-sementioning
confidence: 99%
“…It has already been demonstrated that DNA molecular machines can be controlled using electrical signals, using electrochemical control of pH and pH-sensitive structures such as imotifs or triplexes 14,15 or electronically triggered release of a signalling species from a surface 16 . In an alternative architecture, an enzymatic logic gate under certain conditions produces NADH, which activates an electrochemical process that leads to release of DNA from an alginate matrix 17 .…”
Section: Introductionmentioning
confidence: 99%
“…7-12), primarily because of cytosine protonation reducing electrostatic repulsion, makes DNA triplex structures useful intermediates in designing amplification systems involving switchable pH, following the early work of Nicoloau [41]. Related work involving a much faster triplex ligation scheme involving disulphide bond formation [42] has been reported [43]. DNA triplexes itself are more widely used as reversible hybridization systems and for the sequence dependent recognition of dsDNA in antiviral and biotechnological applications, and so the extension of mobility control by lipid-DNA to impact dsDNA via triplexes is of more general interest.…”
Section: Programmable Sequence-dependent Gel Mobility Using Triplex Smentioning
confidence: 99%
“…Polypurine-polypyrimidine sequences can fold into triple helical DNA structures forming T-A-T and C-G-C + nucleobase triplets upon protonation of cytosine bases at pH ≤ 6. 1 The predictable and pH-controlled base pairing makes triplex-forming sequences very useful for programming chemical reactions, 2,3 nanomachines, 4,5 nanostructures, [6][7][8] and hydro-gels. 9,10 Switching of pHresponsive DNA composites can be employed for controlled release of targets in delivery systems 11,12 and in on/off regulation of the nanoscale devices upon cyclic alternation of pH values.…”
mentioning
confidence: 99%
“…17 For the latter, the assay time can be reduced to 10-15 min using capillary gel electrophoresis. 3,9 Palindromic homopurine-homopyrimidine tracts have been shown to cause a pHdependent structural transition of a plasmid DNA in vivo and have been observed during the initial replication of tumor viruses. 20 Therefore, dosedependent detection of polypurine tracts (PPT) in human and viral genomes can contribute to molecular diagnostics of genetic biomarkers such as the conserved PPT region of HIV-1.…”
mentioning
confidence: 99%